Q: What is 3t plus 2s plus t plus 5s?

Write your answer...

Submit

Related questions

That's a simple example of system of equations. There are quite a number of methods for solving those, but the easiest here would be to calculate one variable from first equation and substitute it into second. 2s + 3t = 28 5s + 6t = 61 Let's calculate s from the first equation: 2s + 3t = 28, 2s = 28 - 3t s = 14 - 3t/2 Substitute s into second equation 5s + 6t = 61, 5(14 - 3t/2) + 6t = 61, 70 - 15t/2 + 6t = 61, 70 - 3t/2 = 61, 3t/2 = 9, t = 6. We can then substitute t back into first equation: 2s + 3t = 28, 2s + 3 * 6 = 28, 2s = 10, s = 5. So the final answer is: s = 5 t = 6

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

s = 7, t = -3

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

4

17

5t + 1

3t+11 = 29 3t = 29-11 3t = 18 t = 6

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

t = -11/10

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

As it is written, it makes no sense. If you mean: (s)(3t)(2s-2t) then the answer is 6s^2t - 6st^2 or (6st)(s-t) If the statement is something else, then the answer is something else

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

Gather like terms: 3t - t = 13 - 4 ie 2t = 9 so t =4½ Check: 3t = 13½ + 4 = 17½, 4½ +13 = 17½ QED

(3t + 1)(t + 5)

It is: 3(t+3)

bt + 5b - 3t - 15 = b(t + 5) - 3(t + 5) = (t + 5)(b - 3)

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

It is the same as: 2s = t

If you simplify the equation (s+t+s) the answer is 2s+t

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

-(t(3t + 1)(t - 8))

8

T + 5 + 3T = 1 Simplify the terms, T and 3T (think 1 apple plus 3 apples) 4T + 5 = 1 Subtract 5 from both sides. 4T = -4 then divide both sides by 4 to get T by itself. T = -4/4 T = -1 To check, substitute T = -1 wherever you see T in your original equation. T + 5 + 3T = 1 (-1) + 5 + 3(-1) = 1 4 - 3 = 1 1 = 1 (check)

t+5+3t = 1(subtract 5 from each side)t+3t = -4(combine like terms)4t = -4(divide both sides by 4)t = -4/4t = -1